Peningkatan Prestasi Siswa melalui Pengembangan Profesional Guru: Suatu Tinjauan Literatur - Yuni Kasmawati (Jurnal Maksipreneur, 2020)
Currently, teachers are required to carry out their professional development. Because of professional development is a continuous learning process, so the teacher will learn the best way to adapt their teaching skills to fulfill student learning needs. The method used in this research is a literature review by utilizing reference sources in the form of journals, books, and other forms of publications. This study aims to examine the importance of teacher professional development in an educational environment that is used as a strategy to improve teacher capacity and student achievement. The results of this study indicate that professional development plays an important role in improving student achievement. However, increasing student achievement must be preceded by changes in teacher capacity, such as their knowledge, skills, attitudes, and beliefs that will bring changes in teaching and learning activities. Furthermore, teacher capacity can improve student achievement, so that in turn some improvements for school quality will be achieved in order to achieve overall educational success.